Znaczenie profesjonalizacji zawodowej animatorów kultury - Cyboran, Beata (Adult Education Discourses, 2020)
Socio-cultural animation, as an innovative means of organising social and cultural activities, became popular in Poland in the beginning of the ‘90s of the 20th Century. It was the first, and probably the only answer (complimentary to the social change occurring due to the transformation) to the dominating in the Polish People’s Republic (PPR) concept of centralised cultural propagation. The innovativeness of the discussed approach influenced both the theory and practice of socio-cultural activity. As a result of them, there are academic curricula in the field of cultural animation, many institutions working on socio-cultural activity changed names, and many events were organised to foster the experience-sharing about this idea among theorists and practitioners. Part of the reflection was also devoted to those who are cultural animators, socio-cultural animators, and social animators. This professional profile was characterised in many ways by assigning it specific knowledge, skills and social competences. The process of professionalising the careers of cultural animators can be interpreted in two different ways. From one point of view, as a profession associated with non-institutional activity, it should not be subject to professionalisation. On the other, active animators of the “young generation” do not want to reconcile with identifying their professional activities with non-professional and volunteer work. The tension between these two approaches has been evident for many years. Currently, it resounds more and more due to the decreasing interest in working as an animator and the weakening interest of young people in education in fields connected to culture animation. This is good time to ask again about the level of professionalisation of cultural animators in Poland. .